EFEKTIVITAS GAMIFIKASI BERBASIS QUIZIZZ DALAM PEMBELAJARAN QAWA’ID RASM AL-IMLA’ - Baiq Raudatussolihah (Program Studi Pendidikan Bahasa Arab, 2026)
The development of digital technology has brought significant changes in the world of education, including Arabic language learning in universities. One of the emerging innovations is the use of Quizizz-based gamification in learning qawa’id Rasm al-Imla’. This study aims to determine the effectiveness of using Quizizz in improving the understanding, motivation, and learning outcomes of Arabic Language Education students at Makassar State University (UNM) on Rasm al-Imla’ material. The study used a quantitative approach with a quasi-experimental method through a pretest-posttest control group design. The research subjects consisted of students of the Arabic Language Education Study Program at UNM who were divided into experimental and control classes. Data collection techniques were carried out through tests, observations, and questionnaires. The results showed that the application of Quizizz-based gamification was able to increase student engagement in learning, strengthen learning motivation, and improve learning outcomes significantly compared to conventional methods. Thus, Quizizz is effectively used as an innovative learning medium in learning qawa’id Rasm al-Imla’.